Acupressure as an Adjunct to Pharmacological Treatment for Depression, Anxiety, and Stress in Patients with Knee Osteoarthritis - Meenu Rani; Lokendra Sharma; Uma Advani; Susheel Kumar (Medical Association of Pharmacopuncture Institute, 2020)
Background: Osteoarthritis is the most common type of arthritis. Depression, anxiety, and stress are associated with knee osteoarthritis. Objectives: The aim of the study was to check the effectiveness of acupressure therapy with pharmacological treatment on pain, depression, anxiety, and stress in patients with knee osteoarthritis and to assess the effect of pain improvement on psychological health. Methods: Eligible 212 patients with knee osteoarthritis were divided into two groups (intervention and control group). The intervention group (n = 106) received acupressure therapy in combination with pharmacological treatment, whereas the control group (n = 106) continued pharmacological treatment only. Pain and psychological symptoms were measured using the visual analog scale and Depression Anxiety Stress Scale-21. Pearson's correlation was used to check the effect of pain improvement on psychological health. Results: Patients of both groups reported severe pain initially. On analyzing the results after completion of the study, it was found that patients in the intervention group scored better on the pain scale (p < 0.001) and DASS-21 (p ≤ 0.0001). However, it may be noted that reduction in the DASS-21 score was not found to be significant for the control group (p = 0.08). Pearson's correlation coefficients value ranged from 0.231 to 0.412 for DASS-21 (p < 0.05). Conclusions: On analysis, it can be concluded that acupressure can be used as add-on therapy in combination with conventional treatment (pharmacological treatment), which may assist in pain reduction. The reduction in pain directly contributes to improvement in the physiological wellness among patients with knee osteoarthritis.